Study on Cellulase Production by a Bacillussp. C6 - DILEK OZSAHIN, AYSE; KIRAN, OZLEM (Asian Journal of Chemistry, 2010)
In this study, cellulase activities of Bacillus sp. strains isolated from the samples of soil, water and waste taken from nearby paper-mills in Kahramanmaras have been investigated and techniques to increase enzyme activities have been applied. By performing the intensifying of cellulase from Bacillus sp. strains which show the highest activity of cellulase, enzyme amounts have been investigated. In additional, interval of pH and temperature that enzyme has shown optimum activity has been found. It has been determined that cellulase enzyme performs the optimum activity at pH 10 and 40 ºC temperature. Furthermore, it has been observed that metal ions and concentration of carboxymethyl cellulose have affected enzyme activity.